In situ visualization of sodium transport and conversion reactions of FeS2 nanotubes made by morphology engineering. (June 2019) - Yao, Libing; Xia, Weiwei; Zhang, Hongtao; Dong, Hui; Xin, Huolin L.; Gao, Peng; Cai, Ran; Zhu, Chongyang; Wu, Yi; Nie, Meng; Lei, Shuangying; Sun, Litao; et al.
Abstract: Iron disulfide (FeS2 ), existing in nature as pyrite, holds great promise as a conversion-type anode material for sodium-ion batteries (SIBs), owing to its low cost and high theoretical capacity. However, the large volume expansion and the sluggish electrode reaction kinetics during conversion reactions impede its large-scale practical application in SIBs. Here, we demonstrate the utilization of morphological engineering to achieve poly-crystalline FeS2 nanotubes (NTs) consisting of tiny FeS2 crystallites. In situ transmission electron microscopy observations reveal that 1D shape can afford straight pathways for Na transport to expedite reaction kinetics, and poly-crystalline structure can buffer large volume expansion and structural strain. Furthermore, high-resolution imaging and electron diffraction were utilized to track phase evolution associated with conversion reactions in real time. We have identified an intercalation-conversion reaction mechanism from the FeS2 phase to the Na2 S + Fe phases via the intermediate NaFeS2 phase upon initial sodiation. Impressively, a reversible and symmetric conversion reaction between NaFeS2 phase and Na2 S + Fe phases is established during subsequent sodiation−desodiation cycles. Notably, this is the first report of FeS2 NTs investigated for secondary battery electrode material. This work not only provides valuable insights into sodium storage mechanism of FeS2 material, but also corroborates the pivotal role of morphology engineering in optimizing the microstructure of electrode materials for advanced SIBs. Graphical abstract: Image 1 Highlights: This is the first report of FeS2 nanotubes investigated for secondary battery. In situ TEM visualization of conversion reactions in FeS2 nanotubes is conducted. Morphology engineering improves sluggish electrode reaction kinetics of FeS2 . FeS2 nanotubes exhibit ideal structural stability upon repeated (de)sodiations.